INFLUENCE OF UNSATURATED SOIL PROPERTIES ON ENERGY PILES IN DIFFERENT CLIMATIC CONDITIONS - Abilev, Zheniskan (Nazarbayev University Graduate School of Engineering and Digital Sciences, 2024)
Global warming has been a hot topic of discussion and focus for research among scientists in recent decades because of threats to human health, biodiversity, natural disasters, and so on. One of the primary drivers of global warming is human dependence on the combustion of fossil fuels for energy generation emitting carbon dioxide and other pollutants. The are numerous technologies and new ones emerging that produce green energy without emissions. However, nowadays, green technologies are in the minority. One of the new sustainable technologies is energy piles. The energy pile exploits the thermal stability of deep ground for temperature control inside buildings. This new technology consumes significantly less energy for warming or cooling the building in comparison with conventional methods. The effectiveness of the energy pile can be influenced by external factors, namely initial ground temperature, climatic conditions, heat capacities, and thermal conductivities of the energy pile and soil. This present study examines the influence of climatic conditions and unsaturated soil properties on the efficiency of energy piles. A numerical analysis has been conducted using Sigma/W and Temp/W modules of GeoStudio software for the simulation of energy piles in various conditions. The model was built in axisymmetric 2D. The analysis involved testing of the energy pile in three soil materials in saturated and unsaturated states in cold, moderate, and hot climates. The relationship between moisture content and soil suction was represented using the Soil-Water Characteristic Curve (SWCC) and integrated into a numerical model for soil in unsaturated conditions. In unsaturated soils, the unfrozen water content was determined using the Soil Freezing Characteristic Curve (SFCC). It was found that temperatures in saturated soils are higher than in unsaturated in upper soil layers in moderate and hot climates due to higher water content. In cold climates, the temperature difference was negligible. From a long-term perspective, the effectiveness of the energy pile might diminish because of the reduction of the temperature difference between the energy pile and adjacent soil.
Keywords: type of access: embargo; Unsaturated soil; Energy pile; Different climatic conditions